Genus Sinevia Kerzhner (Hemiptera: Miridae: Bryocorinae) new to Korea - Minsuk Oh; Seunghwan Lee (Journal of Asia-Pacific Biodiversity, 2019)
The genus Sinevia Kerzhner, 1988, is reported from the Korean Peninsula for the first time, with a representative species, Sinevia tricolor Kerzhner, 1988. Diagnostic characters for the genus are provided with the habitus images and female genitalic structures of S. tricolor. Keywords: Bryocorinae, Korean Peninsula, Miridae, New record, Sinevia